Asuhan Keperawatan pada Tn. S dengan Cholelithiasis di Ruang Dahlia RSUD dr. Soeselo Kabupaten Tegal - Sinta Nurlaela; Tati Karyawati; Sujono Sujono (STIKes Ibnu Sina Ajibarang, 2024)
Cholelithiasis or gallostones is a digestive tract disease caused by the accumulation of solid mass deposits in the vesica fellea ar gallbladder. The purpose of this paper is to find out and provide nursing care to Mr. S with cholelithiasis is the dahlia ward of dr. Soeselo hospital, Tegal Regency according to nursing standards. The methods used were interviews, medical history, physical examinations and laboratory examination results and diagnoses to create basic assessment data. From the case review, it was found that the patient’s main complaint was shortness of breath. The nursing problems found were hypervolemia and knowledge deficit. Interventions were arranged based on the theory in SDKI, SLKI and SIKI as well as on the client’s condition and could be implemented.